Access to treatment for hepatitis B virus infection—Worldwide, 2016. Issue 10 (27th September 2018) - Hutin, Yvan; Nasrullah, Muazzam; Easterbrook, Philippa; Dongmo Nguimfack, Boniface; Burrone, Esteban; Averhoff, Francisco; Bulterys, Marc
Abstract : Approximately 10.5% of the 257 million people living with hepatitis B are aware of their infection and only 1 in 6 of those aware of their infection are receiving treatment, potentially creating a large pool of individuals at risk for end‐stage liver disease and hepatocellular cancer.